The function f(x) = 3x^2 and g(x) = x - 3.

fog(x) = f(g(x)) = f(x - 3) = 3*(x -3)^2

gof(x) = g(f(x)) = g(3x^2) = 3x^2 - 3

gof(x) = fog(x)

=> 3*(x -3)^2 = 3x^2 - 3

=> (x - 3)^2 = x^2 - 1

=> x^2 - 6x + 9 = x^2 - 1

=> 6x = 10

=> x = 5/3

**The value of fog(x) = gof(x) when x = 5/3**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now